2013
DOI: 10.5713/ajas.2013.13182
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Microbial Population in the Rumen of Dairy Steers as Influenced by Plant Containing Tannins and Saponins and Roughage to Concentrate Ratio

Abstract: The objective of this study was to investigate microbial population in the rumen of dairy steers as influenced by supplementing with dietary condensed tannins and saponins and different roughage to concentrate ratios. Four, rumen fistulated dairy steers (Bos indicus) were used in a 2×2 factorial arrangement in a 4×4 Latin square design. The main factors were two roughage to concentrate ratios (R:C, 60:40 and 40:60) and two supplementations of rain tree pod meal (RPM) (0 and 60 g/kg of total DM intake). Chopped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 38 publications
4
32
0
1
Order By: Relevance
“…The fibrolytic species selected have been widely used as model organisms to study ruminal cellulose digestion. They seem to be representative for the properties and characteristics of the rumen cellulolytic population (Russell et al, 2009) although they comprise only a small part of the total rumen bacteria population (< 1 %; Anantasook et al, 2013;present study). The functional properties of the remaining fibredegrading bacteria species in the rumen and the hindgut are less well known.…”
Section: Differences In Microbial and Fermentation Characteristics Bementioning
confidence: 77%
See 1 more Smart Citation
“…The fibrolytic species selected have been widely used as model organisms to study ruminal cellulose digestion. They seem to be representative for the properties and characteristics of the rumen cellulolytic population (Russell et al, 2009) although they comprise only a small part of the total rumen bacteria population (< 1 %; Anantasook et al, 2013;present study). The functional properties of the remaining fibredegrading bacteria species in the rumen and the hindgut are less well known.…”
Section: Differences In Microbial and Fermentation Characteristics Bementioning
confidence: 77%
“…Saro et al, 2012;Anantasook et al, 2013). The quantitative influence of different forage types on the abundance of the microbial populations is less well known and has been mainly shown in mixed forage-based diets (Kong et al, 2010, Saro et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…With this, the number of bacteria becomes greater, as the predation by protists, especially ciliates, also decreases; consequently, the feed degradation in the rumen becomes more efficient, due to the existence of a larger number of bacteria acting directly on the feed consumed (Bodas et al, 2012). García-González, González, and López (2010) and Anantasook, Wanapat, Cherdthong, and Gunun (2013) reported that the increase of Gram-negative bacteria improves the fermentation of nutrients in the rumen, consequently causing an increase in the digestibility of dry matter and organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact of maintaining desired amount at rumen-reticulum in specified period for to overcome foaming (Reid, 1958). Supplementation of rain tree pod meal and different concentrate ration had decreased pH, protozoa and methanogens among dairy steers (Anantasook et al, 2013). Studies by refer that rumen pH of less than 6.2 have effect on microbial synthesis and cellulose digestion.…”
Section: Scientific Assessment Of Technologies In Treatment Of Bloatmentioning
confidence: 99%
“…The use of trace elements like Zinc and copper for performance enhancement resulted in impairment of plant production, accumulation in animal products, water supply chain and antimicrobial resistance (Brugger and Windisch, 2015). Reducing methane emission by enhancing feed digestibility through rumen microbial ecosystem is pertinent (Anantasook et al, 2013). Evidences to initiate further experiments to understand role of indigenous system in reducing GHG were shared (Ravikumar et al, 2015c).…”
Section: Ikrs and Environmental Responsibilitymentioning
confidence: 99%